Urban Green Spaces and Mental Health: Sociological Perspectives from Bandung Residents - Mustofa, Zainal (Generasi Sains Indonesia, 2025)
Urbanization in Bandung has reduced the availability of green spaces, creating concerns about residents’ well-being and mental health. Parks, urban forests, and riverside areas serve not only as ecological buffers but also as vital spaces for social interaction and psychological restoration. This study explores how green space use relates to mental health among Bandung residents through a mixed-methods approach. Surveys of 350 respondents measured visit frequency, accessibility, and perceived well-being, while interviews and spatial mapping provided deeper contextual understanding. The findings show that over half of residents visit green areas weekly and one-fifth daily, reporting benefits such as improved mood, reduced stress, and greater emotional resilience. Green spaces also strengthen community ties by fostering social interactions. However, issues such as overcrowding, inadequate facilities, and poor maintenance reduce accessibility and satisfaction, while safety concerns limit nighttime use. Overall, urban green spaces play a crucial role in supporting mental health and social cohesion. Enhancing accessibility and management is essential for sustainable and inclusive urban living.